Evaluation of the project to develop a public health service system for prisoners in prisons - Phoglad, Saowathan; Sang-arun, Nattapon (Journal of Multidisciplinary Academic Research and Development (JMARD), 2025)
This research aims to evaluate the development of a public health service system for inmates in prisons/correctional institutions, covering at least 30 target prisons across all regions in phases one and two, as well as other prisons not involved in the project. The study involved random sampling of stakeholders, including administrators, project personnel from the Department of Corrections and the Ministry of Public Health, inmates, and prison volunteers. Data was collected from 666 participants through questionnaires and 180 participants through qualitative interviews and focus group discussions, employing statistical principles and purposive selection. The evaluation was divided into two parts: (1) a quantitative analysis assessing the opinions and satisfaction levels of operators and inmates on various issues using descriptive statistics. The results showed high levels of satisfaction, with mean scores of 4.25 for inmates and 4.22 for operators; and (2) an evaluation of project implementation results using the CIPP Model. This included both quantitative methods, conducted through descriptive statistics, and qualitative methods, which involved document and content analysis. Overall, the development of the public health service system for inmates was found to be positive and successful in many aspects, achieving mean satisfaction scores of 4.05 for inmates and 4.09 for operators. However, some indicators remained unimplemented in certain areas due to limitations in personnel, budget, and location. A health economic evaluation revealed that the primary benefits of the project lie in quality improvements (Ordinal Approach). A cost-effectiveness analysis (CEA) indicated that the total project cost was 335,645,663 baht, resulting in enhanced efficiency across 34 performance indicators related to public health services in prisons, which positively impacted the lives of 108,146 inmates by improving their living standards. In conclusion, this research study offers three sets of recommendations: (1) for implementing the Good Health, Good Heart Project to enhance public health services for inmates; (2) for the operational development of these services involving three key stakeholders: prisons/correctional institutions, network hospitals, and local agencies; and (3) policy recommendations for future enhancements of public health services for inmates.